Pengaruh Durasi Penggunaan Media Sosial Terhadap Pola Komunikasi Generasi Milenial : Studi Kasus Akun Instagram @Folkative - Dea Wulan Saummi; Ilah Holilah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This article discusses the impact of social media usage duration on the communication patterns of the millennial generation, focusing on the Instagram account Folkative as a case study. In the digital era, social media has become the primary platform for millennials to interact and express themselves. This research identifies how the time spent on social media influences the way young people communicate, both digitally and face-to-face.Through content analysis and user engagement on Folkative, it was found that the duration of social media use correlates positively with engagement levels and changes in communication style, such as an increase in informal language and visual content. However, the study also notes emerging challenges, including a decline in face-to-face communication skills and mental health risks due to social media dependence. These findings highlight the importance of a deep understanding of social media's effects on millennial communication patterns and the need for strategies to maximize benefits while minimizing risks associated with social media use.